An evaluation of the 2010 federation of international Football associations (FIFA) World Cup™ on business establishments : a case study of a suburb in Cape Town - Hendricks, Nuraan (Cape Peninsula University of Technology, 2017)
Thesis (MTech (Tourism))--Cape Peninsula University of Technology, 2015. === Local business concerns and perceptions are generally neglected in relation to mega-event research, as most studies have, so far, focused on the broader economic impacts, as well as on the social impacts, and, more recently, on the environmental impacts of mega-events. South Africa being afforded the opportunity to host the 2010 FIFA World Cup™ created much excitement for all, and especially so for the business market. This is because the market in question is at the forefront of providing goods and services to the much anticipated increased number of tourists, whether such goods and services consist of the provision of accommodation, food and beverage, or entertainment, as well as ancillary products and services. The focus of the study was on gaining an understanding of the awareness and the impacts of the 2010 FIFA World Cup™ on businesses, especially those situated within close proximity of the Cape Town Stadium. The study was conducted three months before, and three months after, the event. The investigation explores the level of perceptions, attitudes, and experiences of the businesses in relation to the 2010 FIFA World Cup™, while simultaneously highlighting their experiences with the event. The primary objective of this approach was to ascertain whether there were any changes between the initial perceptions, and the experiences, among businesses in relation to the event. The five objectives guiding the study involved investigating: (1) business managers’ and owners’ perceptions and experiences of the event; (2) the impacts of the World Cup on businesses; (3) the level of business support for the event; (4) the impacts of leveraging initiatives on businesses; and (5) recommendations aimed at maximising the opportunities granted by future mega-events for businesses. During the pre- and post-event study, a total of 145 surveys were administered to the business owners and managers of SMMEs, using the stratified random sampling method, of which, 72 responded during the pre-event study and 104 during the post-event study.